Dynamic Proteomic Profiling of Extra‐Embryonic Endoderm Differentiation in Mouse Embryonic Stem Cells. (23rd June 2015) - Mulvey, Claire M.; Schröter, Christian; Gatto, Laurent; Dikicioglu, Duygu; Fidaner, Isik Baris; Christoforou, Andy; Deery, Michael J.; Cho, Lily T. Y.; Niakan, Kathy K.; Martinez‐Arias, Alfonso; Lilley, Kathryn S.
Abstract: During mammalian preimplantation development, the cells of the blastocyst's inner cell mass differentiate into the epiblast and primitive endoderm lineages, which give rise to the fetus and extra‐embryonic tissues, respectively. Extra‐embryonic endoderm (XEN) differentiation can be modeled in vitro by induced expression of GATA transcription factors in mouse embryonic stem cells. Here, we use this GATA‐inducible system to quantitatively monitor the dynamics of global proteomic changes during the early stages of this differentiation event and also investigate the fully differentiated phenotype, as represented by embryo‐derived XEN cells. Using mass spectrometry‐based quantitative proteomic profiling with multivariate data analysis tools, we reproducibly quantified 2, 336 proteins across three biological replicates and have identified clusters of proteins characterized by distinct, dynamic temporal abundance profiles. We first used this approach to highlight novel marker candidates of the pluripotent state and XEN differentiation. Through functional annotation enrichment analysis, we have shown that the downregulation of chromatin‐modifying enzymes, the reorganization of membrane trafficking machinery, and the breakdown of cell–cell adhesion are successive steps of the extra‐embryonic differentiation process. Thus, applying a range of sophisticated clustering approaches to a time‐resolved proteomic dataset has allowed the elucidation of complex biological processes which characterize stem cell differentiation and could establish a general paradigm for the investigation of these processes. Stem Cells 2015;33:2712—2725 Abstract : Here we report a time‐resolved, global proteomic map of cellular change during the directed differentiation of mouse ES cells into extraembryonic endoderm‐like cells induced by forced GATA factor expression. This study reveals that transition from the pluripotent to the differentiated state is accompanied by the downregulation of chromatin‐modifying enzymes and cell‐cell adhesion molecules, and by the successive upregulation of proteins involved in extracellular matrix biogenesis, membrane trafficking and the tricarboxylic acid cycle, as well as an increase in MAPK signaling.